The characteristics of Shorea macrophylla’s habitat in Tane’ Olen, Malinau District, North Kalimantan Province, Indonesia - Muhammad Fajri; Pratiwi PRATIWI; Yosep Ruslim (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fajri M, Pratiwi, Ruslim Y. 2020. The characteristics of Shorea macrophylla’s habitat in Tane’ Olen, Malinau District, North Kalimantan Province, Indonesia. Biodiversitas 21: 3454-3462.  Shorea macrophylla is a tree species in Tane' Olen forest area. This study analyzed the soil’s physical and chemical properties, topography, and microclimate of S. macrophylla’s habitat. A purposive method was used to select a sampling plot and to place the subplots. Soil was analyzed to determine the physical properties, i.e., texture, bulk density, porosity, and water content, and the chemical properties, i.e., pH, CEC, total N, organic C, C/N ratio, P, K , and Al saturation. Importance value index was determined for each tree species to know the species composition in the study site. Only the dominant species were presented. The soil at the study site had bulk density of 0.60-1.31 gram cm³-1, porosity 50.60%-77.35%, water content 34.88%-95.37%, and soil texture sandy clay. The chemical properties of the soil were as follows: pH was 3.6-4.8, N 0.05%-0.19%, organic C 1.40%-3.65%, P 0.41-1.22 mg 100 gr-1, K 58.68-232.55 mg 100 gr-1, and Cation Exchange Capacity (CEC) 5.35-10.81 meg 100gr -1. Slope ranged between 0 and 25%. The microclimate characteristics were as follows: temperature was 24-26.5°C, relative humidity 76-87%, and light intensity 145-750 Lm. Trees species with an IVI ? 10% were S. macrophylla, Madhuca spectabilis, Myristica villosa Warb, Scorodocarpus borneensis, Eugenia spp., Palaquium spp., Macaranga triloba, Syzygium inophyllum and Shorea sp. Positive associations were observed between S. macropylla and S. borneensis, Eugenia spp., Palaquium spp.. and M. triloba, and negative associations were observed between S. macropylla and M. spectabilis, M. villosa Warb, S. inophyllum, and Shorea sp. S. macrophylla grows on riversides with flat and gentle topography, acidic soil, and lower fertility but with suitable microclimate. This species can be recommended to be planted in degraded tropical forest areas but the microclimate and soil properties should be taken into account.